PERSEPSI WISATAWAN TERHADAP OBJEK WISATA PANTAI DI TAMAN WISATA ALAM PULAU POMBO KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Asni Wati; Henderina Lelloltery; Thomas Melianus Silaya (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Pombo Island Nature Tourism Park is a natural tourism destination with great potential for development, but increasing the number of tourist visits in the future has the potential to put pressure on the quality of attractions, accessibility, and supporting tourist facilities. Therefore, an evaluation of tourist perceptions is needed as a basis for sustainable area management. The purpose of this study was to determine tourist perceptions of the 3A components (Attraction, Accessibility, Amenity) in Pombo Island Nature Tourism Park . The research method used Accidental Sampling with a sample of 44 respondents. Tourist perception data were collected using a 5-point Likert scale questionnaire and analyzed descriptively quantitatively, while the results of observations, interviews, and documentations were analyzed descriptively qualitatively. The results showed that tourist perceptions of the 3A components were generally in the good category. The highest score was obtained by the Accessibility component (4.07), followed by Attraction (4.04), while Amenity received the lowest score (3.71). The aspect of beach cleanliness from garbage and the availability of adequate trash bins are the main aspects that need to be improved. The conclusion of this study is that Pombo Island TWA has natural attractions and good accessibility, but requires improvements in supporting facilities and waste management to achieve sustainable tourism management.